Akinwumi Isola. Treasury of Childhood Memories. Translated by Pamela J. Olubunmi Smith. Austin, TX: Pan African University Press, 2016. 192 pp. - Michael Oladejo Afolayan (Yoruba Studies Review)
Review essay of Akinwumi Isola's Treasury of Childhood Memories. Translated by Pamela J. Olubunmi Smith. Austin, TX: Pan African University Press, 2016. 192 pp.